Sampling and analysis of iron, steel and other ferrous metals. Methods of analysis. Sampling and analysis of iron, steel and other ferrous metals. Methods of analysis. Determination of boron. Curcumin spectrophotometric method after distillation Part 3.5.3, (15th January 1998) - British Standards Institution,
No abstract available